2016
DOI: 10.1007/s10712-016-9384-0
|View full text |Cite
|
Sign up to set email alerts
|

Variable Chandler and Annual Wobbles in Earth’s Polar Motion During 1900–2015

Abstract: The Chandler wobble (CW) and annual wobble (AW) are the two main components of polar motion, which are difficult to separate because of their very close periods. In the light of Fourier dictionary and basis pursuit method, a Fourier basis pursuit (FBP) spectrum is developed, which can reduce spectral smearing and leakage caused by the finite length of the time series. Further, a band-pass filtering method based on FBP spectrum (FBPBPF), which can effectively suppress the edge effect, is proposed in this paper.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 56 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…Moreover, we show that the available Atmospheric Angular Momentum (AAM) and Oceanic Angular Momentum (OAM) cannot reproduce the recent CW anomaly. The decreasing trend of the CW amplitude has been already pointed out by some studies (e.g., Wang et al 2016;Malkin and Miller 2010), but it was unclear when the amplitude of CW became almost zero. In addition, no previous studies have examined the impact of AAM/OAM to check if they can account for the recent decrease in CW amplitude.…”
Section: Introductionmentioning
confidence: 85%
“…Moreover, we show that the available Atmospheric Angular Momentum (AAM) and Oceanic Angular Momentum (OAM) cannot reproduce the recent CW anomaly. The decreasing trend of the CW amplitude has been already pointed out by some studies (e.g., Wang et al 2016;Malkin and Miller 2010), but it was unclear when the amplitude of CW became almost zero. In addition, no previous studies have examined the impact of AAM/OAM to check if they can account for the recent decrease in CW amplitude.…”
Section: Introductionmentioning
confidence: 85%
“…Previous investigations have identified anomalies of the CW in the 2010s, with changes in atmospheric excitation suggested to be the likely reason (Wang et al 2016;Zotov et al 2022;Malkin 2023;Yamaguchi and Furuya 2024). In this study, we explored deeper into the factors contributing to the reduction in the CW amplitude.…”
Section: Introductionmentioning
confidence: 92%
“…( 14), the a A and m A are the constants of the annual linear amplitude (Shen et al, 2018), f A = 1/365.25 is the annual frequency, and w A is the un-estimated phase. Instead of the assumption of an initial constant period (e. g., 428 days) in the biaxial rigid Earth (Becker, 1954), the later double-periods motion (e.g., 428 and 438 days) with the beat model (Colombo and Shapiro, 1968) or the recent variable period (e.g., from 392 to 441 days) under the sustained excitation (Wang G. et al, 2016), the MH fitting for CW was postulated as 5-period channels (namely, M = 5, Pan. 2007;Zhang et al, 1986) of T main {432 days}, T 1,0 and T 1,1 {symmetrical peaks: 429 and 435 days}, and T 2,0 and T 2,1 {symmetrical peaks: 406 and 447 days}.…”
Section: Figurementioning
confidence: 99%
“…Such Chandler frequency splits respond to the coupled oscillators in the triaxial or axially near-symmetrical Earth and are indeed equivalent to amplitude or frequency modulation (Pan, 2012). In routine practice, the CW was generally considered to have a fixed or time-varying frequency; for high-precision prediction, however, such choices may also introduce deviations (Malkin and Miller 2010;Wang G. et al, 2016). Akyilmaz et al (2011) further showed that the quasi-periodic and irregular processes in the PM residual need to be settled for prediction.…”
Section: Introductionmentioning
confidence: 99%